The Steglich Rearrangement of 2‐Oxindole Derivatives Promoted by Anion‐based Nucleophilic Catalysis. Issue 16 (17th June 2019) - Trujillo, Cristina; Litvajova, Mili; Cronin, Sarah A.; Craig, Ryan; Connon, Stephen J.
Abstract: The first small anion‐triggered Steglich rearrangements are reported. Tetrabutylammonium carboxylates‐, cyanide‐ and fluoride promote the O ‐ to C ‐acyl transfer of a range of O‐acylated oxindoles to form 3, 3‐disubstituted oxindole products with new quaternary stereocentres. DFT calculations on the TBAF‐mediated reaction strongly support a nucleophilic catalysis mechanism involving initial attack of fluoride on the O ‐acyl group to give an enolate and an acyl fluoride in the rate determining step. Abstract : Small but mighty : An experimental and computational DFT study has shown that O ‐ to C ‐acyl transfer in 2‐oxindole derivatives is promoted by fluoride via a nucleophilic catalysis mechanism.Ruble, G. C. Fu, J. Am. Chem. Soc ., 1998, 120, 11532.